Unraveling the immune evasion mechanisms in the tumor microenvironment of head and neck squamous cell carcinoma - Zhao, Xuri; Zhu, Yaping; He, Youya; Gu, Weiyan; Zhou, Qi; Jin, Bei; Chen, Shenguo; Lin, Haisheng (Frontiers in Immunology, 2025)
Head and neck squamous cell carcinoma (HNSCC) is a highly aggressive malignancy characterized by a complex tumor microenvironment (TME) that plays a pivotal role in tumor initiation, progression, and immune evasion. Recent advancements have highlighted the intricate interplay between immune cell infiltration patterns, immune checkpoint dysregulation, and metabolic reprogramming in driving HNSCC immune escape. Despite these insights, significant challenges remain, including the incomplete understanding of specific immune evasion pathways and the lack of personalized therapeutic strategies. To address these gaps, this review introduces a novel “Trinity” regulatory network of immune evasion in HNSCC, encompassing: (1) metabolic reprogramming-mediated immune checkpoint modulation, (2) stromal cell-driven immune dysfunction, and (3) epigenetic remodeling fostering immune tolerance. This framework provides a theoretical foundation for the development of multi-targeted combination therapies and offers innovative strategies to overcome immune evasion. Additionally, this review systematically synthesizes the current understanding of the relationship between the HNSCC microenvironment and immune escape, with a focus on emerging immunotherapeutic approaches such as PD-1/PD-L1 inhibitors and CAR-T cell therapy. Leveraging cutting-edge single-cell sequencing and spatial transcriptomics, we elucidate the spatiotemporal heterogeneity of the HNSCC immune landscape and propose a new paradigm of “lineage plasticity-driven immune adaptation.” These insights not only advance our understanding of HNSCC biology but also pave the way for the development of precision immunotherapies aimed at improving patient survival and quality of life. By integrating multidisciplinary perspectives, this work underscores the importance of targeting the TME to achieve durable clinical responses and overcome immunotherapy resistance in HNSCC.